Clinical impact of the switch from femoral to radial approach for coronary intervention: a single-center experience. (February 2015) - Aldalati, Omar; Kallas, Khaled; Nashat, Heba; Khalil, Sajad; Ionescu, Adrian
Aim: To evaluate the safety profile during a 3-year transition from default transfemoral access to default transradial access (TRA) for percutaneous coronary interventions in a tertiary cardiac center.Methods: Data were collected from electronic databases on all percutaneous coronary interventions from 2007 to 2009.Results: Two thousand eight hundred and forty-five procedures were recorded. TRA increased from 36 to 58% of procedures over the study period. Postprocedure blood transfusion requirements, incidence of hematoma and hospital length of stay were less among TRA cases. Fluoroscopy time, procedure time and mortality were similar in both groups. Access site crossover was higher among TRA cases but not prohibitive.Conclusion: Transitioning from a default transfemoral access to TRA unit was not associated with an adverse clinical or safety profile.